Electrodeposited coating from Vietnamese raw materials-pigmented system - Bắc, Nguyễn Việt; Minh, Đào Công; Hữu, Chu Chiến (VNU Journal of Science: Natural Sciences and Technology; Vol 11 No 2, 1995)
Abstract